Overall training workout indicators of elite junior national waterpolo team: Serbian model for 2007 season - Dopsaj, M.; Vasilovski, N.; Manojlovic, N. (1st International Scientific Conference of Aquatic Space Activities, 2008)
The aim of this study was to define and specify the values of the indicators of overall training workout for the Serbian junior national waterpolo team in 2007 season, for the purpose of improving technology management. During the 90-day period between Jun 18, 2007 and Sep 15, 2007, the team had 75 pure training practice days with the total of 160 single training units, which included 88 training units in water, 41 training units outside water, and 31 games (where 8 were training games, 4 were official training games, and 19 were competitive games). In total, the team did 237 h 49 min of practice work, out of which 198 h 13 min were in the swimming pool (including the games) and 39 h 36 min were dryland work. Besides, the team members realised overall training load by swum total of 375.64 km (including the games), with an average of 3.157 km per single training unit. According to the time structure, players realised an average of 4 h and 6 min of training workouts per single training practice day, or 1 h 39 min 56 sec per single training unit in water (including the games days) and 57 min 57 sec per single training unit outside water. ITE index, the coeficient of pure training (practice) efficiency was at the index level of 0.3164 ± 0.1755.